Effects of Griseofulvin in the Treatment of Lichen Planus -A Study in BSMMU - Sen, KG; Hira, RM; Islam, AZMM; Sarker, SK; Sarker, MN; Biswas, AK (Faridpur Medical College Journal, 2011)
Lichen Planus (LP) is an inflammatory disorder of skin, mucous membranes, nails and hair. There are various modalities of treatment but none is curative. This prospective therapeutic trial was done among patients with lichen planus at the outpatient department of Dermatology & Venereology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka between November 2001 and April 2002. Total 20 patients were taken of them 12 were male and 8 were female with male to female ratio 3:2. Age of the patients was between 10 to 50 years. Patients were diagnosed clinically & confirmed histologically. They were treated with griseofulvin 500 mg daily for 6 months. Out of 20 patients, 8 had only oral lesions, of them 2 (25%) showed complete response, 3(37.5%) showed moderate improvement and 4 (37.5%) showed no response. Other 12 patients had lichen planus involving skin without oral mucosa, of them 4 (33.3%) showed moderate improvement, 4 (33.3%) showed no response and 4 (33.3%) patients worsens with treatment. So, success in patients with cutaneous lichen planus is less likely; however, griseofulvin may afford relief in selected patients with oral lesion. This study indicates that further prospective placebo controlled studies are needed to clarify the efficacy of griseofulvin in lichen planus. Key words: Lichen planus; Griseofulvin DOI: http://dx.doi.org/10.3329/fmcj.v6i2.9207 FMCJ 2011; 6(2): 86-88